Development of a Methodological Quality Criteria List for Observational Studies: The Observational Study Quality Evaluation - Drukker, Marjan; Weltens, Irene; van Hooijdonk, Carmen F. M.; Vandenberk, Emma; Bak, Maarten (Frontiers in Research Metrics and Analytics, 2021)
Abstract Background. Existing study quality and risk of bias lists for observational studies have important disadvantages. For this reason, we developed a comprehensive widely applicable quality assessment tool for observational studies. Methods. Criteria from three quality lists were merged into a new quality assessment tool: the Maastricht Observational study QUality Evaluation (MOQUE). The MOQUE consists of a cohort, case-control, and cross-sectional version. Results. The MOQUE cohort, the MOQUE case-control and the MOQUE cross-sectional include all items applicable to that type of study, for example the representativeness of the study population, the validity of the independent and dependent variables, and the used statistical methods. Before scoring the MOQUE, the rater is asked to define how to score items, in detail. A study can obtain a star for each item. Each item also has a veto cell. This cell can be checked when poor quality with respect to that specific item results in a low quality despite stars on other items. Although stars add to a sum score, the comments field is the most important part of the MOQUE. Conclusions. The MOQUE presented in the current paper provides a short, comprehensive and widely applicable list to assess study quality and therewith risk of bias.